Two new species of the feather mite genus Analloptes (Trouessart, 1885) (Acariformes: Astigmata: Xolalgidae) from passerines (Aves: Passeriformes) in Brazil - Mironov, Sergey (2014)
Two new feather mite species of the genus Analloptes Trouessart, 1885 (Acariformes: Xolalgidae) are described from suboscine passerines (Passeriformes) in Brazil: Analloptes giganteus sp. n. from Conopophaga lineata (Wied) (Conopophagidae) and A. cnemotricci sp. n. from Cnemotriccus fuscatus (Wied) (Tyrannidae). These are the first Analloptes species described from passerine hosts. Within the genus Analloptes, the two described species constitute a distinct species group characterized by the presence of setae ve and c1 in both sexes and by having the paragenital apodeme free from coxal structures in males.